Relationship between body composition and postural disorder in goalball athletes: Pilot study - Đorđević Stefan; Mitrović Nebojša; Zrnzević Jovana; Kudlaček Martin; Jorgić Bojan (University Educons, Faculty of Sports and Tourism, Novi Sad, 2018)
Goalball is one of the most popular ball sports for people with visual disability. Like other sports, goalball offers the benefit of developing one's physical abilities as well as affecting overall development; however, due to its specific characteristics, it can also have undesirable side effects. In view of this fact, the objective of this study was to determine the relationship between the parameters of body composition and postural status in goalball players. The study participants included 38 male goalball players with the mean age of 27.89 ± 8.4 competing at the international and national levels of goalball representation Group C. The measuring tool TANITA TBW 300 was used to assess body composition parameters, whereas the Spinal Mouse instrument was used for the assessment of postural status parameters among the goalball players. In order to assess the correlation between the two sets of variables (body composition and postural status), correlational analysis between two sets of variables was used. The obtained results reveal a correlation at the level of significance p=0.05 between the angle of the scoliotic curvature in the thoracic area of the spinal column on the one hand, and body mass index on the other, whereas the correlation of body fat percentage and the mass was at the level of p=0.01. No statistically significant correlation was found between the remaining variables. The results obtained indicate increased incidence of deformity both in the sagittal and in the frontal planes of the spinal column; furthermore, the testing of body composition parameters pertaining to fat returned very high results in this group of goalball players.